Potential of Neural Stem Cells for the Treatment of Brain Tumors - P. Taupin (Clinical Medicine Insights: Oncology, 2008)
Neural stem cells (NSCs) are self-renewing multipotent cells that generate the main phenotypes of the nervous system, neurons, astrocytes and oligodendrocytes. As such they hold the promise to treat a broad range of neurological diseases and injuries. Neural progenitor and stem cells have been isolated and characterized in vitro, from adult, fetal and post-mortem tissues, providing sources of material for cellular therapy. However, NSCs are still elusive cells and remain to be unequivocally identified and characterized, limiting their potential use for therapy. Neural progenitor and stem cells, isolated and cultured in vitro, can be genetically modified and when transplanted migrate to tumor sites in the brain. These intrinsic properties of neural progenitor and stem cells provide tremendous potential to bolster the translation of NSC research to therapy. It is proposed to combine gene therapy and cellular therapy to treat brain cancers. Hence, neural progenitor and stem cells provide new opportunities for the treatment of brain cancers.